Primary dysmenorrhea and quality of life among university nursing students in Vietnam - Pham, Ba Nha; Luu, Tuyet Minh; Phan, Thi Ngan; Ho, Minh An; Nguyen, Tien Hoang (Frontiers in Global Women's Health, 2025)
BackgroundPrimary dysmenorrhea (PD) is a common gynecological condition affecting many young women, especially university students. It can have significant effects on daily activities and quality of life. This study aims to describe the prevalence and some factors related to PD among female nursing students at Hanoi Medical University and evaluate its impact on students quality of life. The goal is to provide data for developing treatment and prevention strategies for PD in the community, particularly among female university students.MethodsA cross-sectional descriptive study was conducted on all female nursing students at Hanoi Medical University from January 15th to 31st, 2024. A simple random sampling method was used to select 341 participants. The data were collected using a paper survey and analyzed using SPSS software. The chi-square test was used to compare proportions, and difference rates along with 95% confidence intervals (CIs) were applied to evaluate associations between variables.ResultsThe majority of the students were aged 20 years or older, accounting for 72.8%. Most students (73.9%) reported menarche between the ages of 13 and 18. Out of 341 students, the prevalence of PD was 78.6%. Among them, 68.7% reported moderate to severe pain. PD was significantly associated with a family history of menstrual pain (p < 0.001), irregular menstrual cycles (p = 0.02), and frequent caffeine consumption (p = 0.03). Quality of life, assessed using the Q-LES-Q-SF questionnaire, was significantly lower in all domains among students with PD compared with those without menstrual pain (p < 0.05).ConclusionPDis highly prevalent among female nursing students and negatively affects their quality of life. Several modifiable and non-modifiable factors are associated were found to be significantly associated with PD. The findings underscore the need for targeted interventions and further analytical studies to improve reproductive health and well-being among female students.